World-Class Male Sprinters and High Hurdlers Have Similar Start and Initial Acceleration Techniques - Bezodis, Ian N.; Brazil, Adam; von Lieres und Wilkau, Hans C.; Wood, Matthew A.; Paradisis, Giorgios P.; Hanley, Brian; Tucker, Catherine B.; Pollitt, Lysander; Merlino, Stéphane; Vazel, Pierre-Jean; Walker, Josh; Bissas, Athanassios (Frontiers in Sports and Active Living, 2019)
The effect of the inclusion of a high hurdle 13.72 m after the start line on elite sprint start and initial acceleration technique has yet to be investigated or understood. This highly novel study addresses that lack of information in an exceptional manner, through detailed biomechanical analysis of the world’s best sprint and hurdle athletes, with data collected in situ at the 2018 IAAF World Indoor Championships, held in Birmingham, UK. High speed videos (150 Hz) were compared for eight sprinters and seven hurdlers for the start and initial acceleration phase of the finals of the men’s 60 m and 60 m hurdles. Temporal and kinematic data were supplemented by vector coding analysis to investigate mechanisms by which these world-class athletes translate their centres of mass (CM) up to the fourth touchdown post-block exit. The sprinters and hurdlers coordinated their lower limb and trunk movement in a similar manner throughout the start and initial acceleration phases, which contributes new conceptual understanding of the mechanisms that underpin start and initial acceleration performance. Differences between groups were initiated from block set-up, with the hurdlers utilising a larger block spacing, but with the front block nearer to the start line than sprinters. Even after accounting for stature, the biggest differences in the raising of the CM occurred during the block phase, with hurdlers greater than sprinters (difference in vertical CM displacement = –0.037, very large effect size). Subsequent flight phases showed the biggest differences in the translation of the CM, in part due to longer flight times in the hurdlers, whilst the techniques of the two groups generally converged during the ground contact phases of initial acceleration. In highlighting that similar techniques are used by world-class sprinters and hurdlers, despite differing task constraints, this study has provided invaluable insights for scientists, coaches and athletes, that will inform further developments in understanding and practice across both sprints and hurdles.